2022
DOI: 10.1126/sciadv.abm9530
|View full text |Cite
|
Sign up to set email alerts
|

A localized DNA finite-state machine with temporal resolution

Abstract: The identity and timing of environmental stimulus play a pivotal role in living organisms in programming their signaling networks and developing specific phenotypes. The ability to unveil history-dependent signals will advance our understanding of temporally regulated biological processes. Here, we have developed a two-input, five-state DNA finite-state machine (FSM) to sense and record the temporally ordered inputs. The spatial organization of the processing units on DNA origami enables facile modulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…This FSM allowed precise control of the reactions along predefined paths on the DNA origami structure for different input orders, resulting in minimized leakage and fast kinetics. 61 Some strategies demonstrated FSMs enabling rearrangement of other functional materials (e.g., metal nanoparticles) based on SDR-mediated DNA structural reconfigurations. For example, Kuzyk et al reported a DNA-fueled reconfigurable three-dimensional plasmonic metamolecule.…”
Section: Fsms Based On Individual Dna Nanostructuresmentioning
confidence: 99%
See 4 more Smart Citations
“…This FSM allowed precise control of the reactions along predefined paths on the DNA origami structure for different input orders, resulting in minimized leakage and fast kinetics. 61 Some strategies demonstrated FSMs enabling rearrangement of other functional materials (e.g., metal nanoparticles) based on SDR-mediated DNA structural reconfigurations. For example, Kuzyk et al reported a DNA-fueled reconfigurable three-dimensional plasmonic metamolecule.…”
Section: Fsms Based On Individual Dna Nanostructuresmentioning
confidence: 99%
“…In another example, the DNA origami-based FSM was used to sense the temporal orders of two miRNAs (miR21 and miR122), which suggests the potential of DNA FSMs for temporally resolved biosensing and smart therapeutics. 61 Another important challenge in molecular sensing is to achieve high precision and multiplexity in complex physiological environments. Molecular probes generating switchable signals in response to specific cues are desired for such applications.…”
Section: Molecular Detection and Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations